Platelet/Lymphocyte Ratio Predicted Long-Term Prognosis for Acute Upper Extremity Deep Vein Thrombosis from a Retrospective Study - Liu Y; Sun H; Jiang J (Dove Medical Press, 2023)
Yang Liu,* Hongze Sun,* Jianjun Jiang Department of General Surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianjun Jiang, Department of General Surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan, Shandong, 250012, People's Republic of China, Tel +86 18560085133, Email jiangjianjun1995@163.comBackground: In this study, we aimed to determine the mortality risk factors and whether placement of a vena cava filter improves the prognosis of acute upper extremity deep vein thrombosis (UEDVT).Methods: Clinical data and follow-up results were retrospectively analyzed. Cox regression analysis was conducted to identify the risk factors associated with all-cause mortality in all patients and subgroups of patients. Results are expressed as hazard ratio (HR) with 95% confidence intervals (95% CI). Receiver operating characteristic curves (ROC) were used to determine the optimal cut-off value. Kaplan-Meier survival curves were constructed and compared by the Log rank test.Results: The study cohort comprised 109 patients of median age 56 years (47.5, 64.5). The median follow-up time was 25 months (8, 47): 39 patients (35.8%) had died by 12 months, 55 (50.5%) by 36 months, and 60 (55%) by the end of follow-up. Presence of malignancy (HR: 5.882, 95% CI: 2.128- 16.667), D-dimer (HR: 1.56, 95% CI: 1.09- 1.94), platelet/lymphocyte ratio (PLR; HR: 2.02, 95% CI: 1.15- 3.54), and the systemic immune/inflammatory index (SII; HR: 1.471, 95% CI: 1.062- 1.991) were identified as independent risk factors for mortality. Subgroup analysis of patients with malignancy determined gender (HR: 2.936, 95% CI: 1.599- 5.393) and PLR (HR: 1.427,95% CI: 1.023- 1.989) as independent risk factors. Kaplan-Meier analysis showed that the mortality rate was much higher in patients with malignancy, high D-dimer (≥ 0.92ug/mL), high PLR (≥ 291) and high SII (≥ 1487). However, there was no significant difference between patients with and without vena cava filters.Conclusion: In this study, we identified PLR as an new independent predictor of mortality in patients with acute UEDVT. Emergency placement of a vena cava filter did not improve long-term prognosis.Keywords: upper extremity deep vein thrombosis, mortality risk, vena cava filter, malignancy, platelet/lymphocyte ratio